Free radical scavenging potential of Drosera indica L in presence of Dalton Ascites lymphoma (DAL) tumor bearing mice - Asirvatam, Raju; Christina, AJM (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
The aim of the present study was to evaluate the antioxidant role of Drosera indica L. in Dalton Ascites lymphoma (DAL) bearing Swiss albino mice. The effect of ethanol and aqueous extracts of D.indica (EEDI and AEDI) were administered at a 250 and 500mg/kg once a day for 14 days, 24h after the inoculation of tumor cell line. After the treatment period, blood was collected from the animals and subsequently the animal were sacrificed for isolation of liver, brain, kidney and lungs for the observation of antioxidant status level. The parameters analyzed were catalase (CAT), superoxide dismutase (SOD), glutathione (GSH), malondialdehyde (MDA), peroxidase (P), total protein (TP) and protein carbonyl content (PCC). Treatment with EEDI and AEDI significantly reduced the levels of MDA and increased the levels of GSH, SOD, CAT, P and TP in cancer induced animal and are similar as that of normal mice. The results suggest that the ethanol and aqueous extract of Drosera indica L. possess significant antioxidant effects in DAL bearing mice